Electrospun Biopolyesters: Hydrophobic Scaffolds with Favorable Biological Response - Azari Pedram; Hosseini Samira; Pinguan Murphy Belinda; O. Martinez-Chapa Sergio (Journal of Public Health International, 2018)
This article reviews electrospun biopolyester scaffolds, focusing on surface hydrophobicity, cell response, and applications in tissue engineering.